Pengaruh Belanja Pendidikan, Belanja Kesehatan Dan Belanja Perumahan Dan Fasilitas Umum Terhadap Indeks Pembangunan Manusia (Studi Kasus Pada Pemerintah Daerah Kabupaten Cianjur) - Muhammad Ade Fajar; Lili Indrawati (Indonesian Accounting Research Journal, 2020)
This study aims to determine the effect of education expenditure, health expenditure and housing and public facilities expenditure on the human development index in the Cianjur Regency Government during 2014-2019. The sample is budget realization report and human development index data for 6 years. Data analysis technique used is multiple linear regression analysis SPSS 25.00. The result of this study showed education expenditure, health expenditure and housing and public facilities expenditure simultaneously has positive and significance effect 37,2% of human development index, while 62,8% are effected by other factors. Parcial test result, education expenditure has significant effect of human development index. While health expenditure and housing and public facilities expenditure do not effect of human development index.